Odpowiedź :
[tex]f(x) = 3 - \frac{5}{x}[/tex]
Dziedzina:
[tex]x \neq 0[/tex]
[tex]f(x-1) \ge f(3x-1)[/tex]
[tex] 3 - \frac{5}{x-1} \ge 3 - \frac{5}{3x-1}[/tex]
Dziedzina:
[tex]x \neq 1. x \neq \frac{1}{3}[/tex]
[tex] 3 - \frac{5}{x-1} -3+ \frac{5}{3x-1} \ge 0[/tex]
[tex] - \frac{5}{x-1} + \frac{5}{3x-1} \ge 0[/tex]
[tex] \frac{5}{3x-1} - \frac{5}{x-1} \ge 0[/tex]
[tex] \frac{5(x-1)}{(3x-1)(x-1)} - \frac{5(3x-1)}{(3x-1)(x-1)} \ge 0[/tex]
[tex] \frac{5x-5-15x+5}{(3x-1)(x-1)} \ge 0[/tex]
[tex] \frac{-10x}{(3x-1)(x-1)} \ge 0[/tex]
[tex]-10x(3x-1)(x-1) \ge 0[/tex]
[tex]-10x\cdot\frac{1}{3}(x-\frac{1}{3})(x-1) \ge 0[/tex]
[tex]-\frac{10}{3}x(x-\frac{1}{3})(x-1) \ge 0\ \ \ |:(-\frac{10}{3})[/tex]
[tex]x(x-\frac{1}{3})(x-1) \le 0[/tex]
[tex]x\in(-\infty;0>\cup<\frac{1}{3};1>[/tex]
Po uwzględnieniu [tex]x \neq 1. x \neq \frac{1}{3}[/tex]
[tex]x\in(-\infty;0>\cup(\frac{1}{3};1)[/tex]